Research of the Influence of Design Parameters of a Scraper Conveyor with an Upper Working Branch on its Technical Characteristics - Bogomaz, V. M.; Nagachevskyi, V. J. (Science and Transport Progress, 2025)
Purpose. The research is aimed at: determining the nature of the influence of design parameters on the technical characteristics of a scraper conveyor with an upper working branch (width, height of the chute and drive power); building analytical dependencies of these values on the design characteristics: type and physical and mechanical properties of the cargo, transportation length, productivity, angle of inclination of the route; conducting a graphical analysis of the nature of the influence. Methodology. To achieve this goal, we used the calculation algorithms presented in the modern technical literature, analyzed the factors and values that affect the value of the drive power and the geometric parameters of the conveyor chute. It has been established that to determine the drive power of vibratory conveyors, it is necessary to carry out a detailed calculation, which includes: the width and height of the chute, the pitch and height of the scrapers, the forces at the characteristic points of the route by the method of traversing the contour, and the resistance to load movement. Findings. For a scraper conveyor with an upper working branch designed to transport unsorted coal, a graphical analysis of the influence of the transportation length, the angle of inclination of the route, and productivity on the drive power and geometric dimensions of the chute was carried out. It was found that the function of change in the width of the conveyor chute on the capacity is increasing (with other parameters fixed), and on the angle of inclination - a stepwise increasing function; the function of change in the drive power on the capacity and length of transportation - linearly increasing, on the angle of inclination of the route - nonlinearly increasing. Originality. The author first studied the dependence of drive power and chute width of a scraper conveyor with an upper working branch, built analytical dependencies of technical characteristics (drive power, chute width and height) on design parameters: productivity, transportation length, type and physical and mechanical properties of the transported cargo, and the angle of inclination of the route. For a conveyor that transports unsorted coal, graphical dependencies of the chute width and drive power on the capacity, transportation length, and route angle were constructed. Practical value. The use of the constructed dependencies makes it possible to determine the general nature of the change in the above technical characteristics in the case of varying design parameters such as capacity, conveyor length, and angle of inclination. The proposed dependencies can be used to quickly determine the rational power of the conveyor drive for specific design data.